Prenatal exposure to a mixture of different phthalates increases the risk of mammary carcinogenesis in F1 female offspring - de Freitas, Thiago [UNESP]; Zapaterini, Joyce R. [UNESP]; Moreira, Cristiane M. [UNESP]; de Aquino, Ariana M. [UNESP]; Alonso-Costa, Luiz G. [UNESP]; Bidinotto, Lucas T. [UNESP]; Kass, Laura; Flaws, Jodi A.; Scarano, Wellerson R. [UNESP]; Barbisan, Luis F. [UNESP] (Elsevier, 2021)
Phthalates metabolites have been detected in the urine of pregnant and breastfeeding women. Thus, this study evaluated the adverse effects of maternal exposure to a mixture of six phthalates (Pth mix) on the mammary gland development and carcinogenesis in F1 female offspring. Pregnant female Sprague-Dawley rats were exposed daily to vehicle or Pth mix (35.22% diethyl-phthalate, 21.03% di-(2-ethylhexyl)-phthalate, 14.91% dibutyl-phthalate, 15.10% diisononyl-phthalate, 8.61% diisobutyl-phthalate, and 5.13% benzylbutyl-phthalate) by gavage at 20 μg/kg, 200 μg/kg or 200 mg/kg during gestational day 10 (GD 10) to postnatal day 21 (PND 21). After weaning (PND 22), some female offspring were euthanized for mammary gland analyses while other females received a single dose of N-methyl-N-nitrosourea (MNU, 50 mg/kg) or vehicle and then tumor incidence and multiplicity were recorded until PND 180. Maternal Pth mix exposure increased the number of Ki-67 and progesterone receptor-positive epithelial cells in the mammary gland from Pth mix 200 at μg/kg and 200 mg/kg groups. In addition, tumor incidence and mean number were higher only in Pth mix at 200 mg/kg when compared to the vehicle-treated group, and percentage of tumor-free animals was lower in Pth mix at 200 μg/kg and 200 mg/kg groups. The findings indicate that perinatal Pth mixture exposure increased susceptibility to MNU-induced mammary carcinogenesis in adult F1 female offspring.
Keywords: Chemically-induced mammary tumor; F1female offspring; Mammary gland development and cancer susceptibility; Phthalate mixture